Therapeutic Targeting of p53-Mediated Apoptosis Pathway in Head and Neck Squamous Cell Carcinomas: Current Progress and Challenges - Ichwan, Solachuddin Jauhari Arief; Bakhtiar, Muhammad Taher; Ohtani, Kiyoshi; Ikeda, Masa-Aki (IntechOpen, 2012)
None